Rasmussen Encephalitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Immunological abnormalities associated with chronic encephalitis, epilepsy, and progressive hemiplegia in a three-year, nine-month old girl are reported from the University of Utah School of Medicine and the Primary Children's Medical Center, Salt Lake City, Utah.